Microhardness analysis of thin metallic multilayer composite films on copper substrates - Lamovec J.; Jović V.; Vorkapić M.; Popović B.; Radojević V.; Aleksić R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Composite systems of alternately electrodeposited nanocrystalline Ni and Cu films on cold-rolled polycrystalline copper substrates were fabricated. Highly-densified parallel interfaces which can give rise to high strength of composites are obtained by depositing layers at a very narrow spacing. The hardness properties of the composite systems were characterized using Vickers microhardness testing with loads ranging from 1.96 N down to 0.049 N. Above a certain critical penetration depth, a measured hardness value is not the hardness of the electrodeposited film, but the so-called „composite hardness“, because the substrate also participates in the plastic deformations during the indentation process. Dependence of microhardness on layer thickness, Ni/Cu layer thickness ratio and total thickness of the film was investigated. Model of Korsunsky was applied to the experimental data in order to determine the composite film hardness. The microhardness increased with decreasing the layer thickness down to 30 nm and it is consistent with the Hall-Petch relation. Layer thickness and layer thickness ratio are the important parameters which are responsible for making decision of the total film thickness.